Comparative Evaluation of Push-Out Bond Strength & Adaptation of A Fiber Post Cemented with Biodentine, MTA & Resin Cement: An in Vitro Study. - Harakh Chand Baranwal; Neeraj Kumar; Prachi Rani; Jyoti Yadav (International Journal of Pharma and Bio Sciences, 2022)
Aim of our study is to evaluate & compare the push-out bond strength and adaptation of a fiber post cemented with Biodentine, MTA, and dual-cure Resin cement. A total of thirty mandibular premolars with a single oval root canal were prepared and obturation was done by AH plus sealer and gutta-percha. The teeth were stored at 37 0C with 100% humidity for one day. The gutta-percha was removed by peeso reamer, leaving at least 4 mm of filling material, and post spaces were prepared by corresponding fiber post drill. The specimens were randomly distributed into (n=10) among each 3 groups. Glass fiber Posts were lutted with three different materials and coronally sealed with glass ionomer cement followed by stored in water for 24 h at 37 0 C. Each tooth was sectioned into 3 parts of 2-mm-thick slices in coronal, middle and apical zone. Push-out bond strength was measured with help of a universal testing machine and evaluated the adaptation by scanning electron microscope after 7 and 28 days. Statistical analysis was done by one-way anova and post hoc test. The push-out bond strength of dual-cure resin and Biodentine was non-significant but higher in comparison to Pro Root MTA. Dual cure resin cement and Biodentine also showed better surface adaptation to post in comparison to MTA. This present study showed that Biodentine can also be used for luting the fiber post as an alternative to dual-cure resin cement.